2021
DOI: 10.1002/adhm.202101663
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Scaffolds for Spinal Cord Applications Exhibit Stiffness‐Dependent Immunomodulatory and Neurotrophic Characteristics

Abstract: After spinal cord injury (SCI), tissue engineering scaffolds offer a potential bridge for regeneration across the lesion and support repair through proregenerative signaling. Ideal biomaterial scaffolds that mimic the physicochemical properties of native tissue have the potential to provide innate trophic signaling while also minimizing damaging inflammation. To address this challenge, taking cues from the spinal cord's structure, the proregenerative signaling capabilities of native cord components are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 76 publications
(85 reference statements)
2
39
0
Order By: Relevance
“…Ideal biomaterials with soft mechanical characterizations, oriented three-dimensional structures, high water content and strong deformation resistance are more favorable for the repair of spinal cord tissues. 32,33 Natural DSC had unique advantages: it had the closest biological components to spinal cord tissue and had good biocompatibility, 34 it had cell membrane receptor recognition sites on the surface that facilitated cell adhesion, growth, and survival, 35 it retained molecules such as collagen, fibronectin, laminin, etc., which can bind to integrins on the surface of the proximal growth cone when implanted in vivo, thereby acting as a short-range axon guiding signal. 17 First, we prepared a rat DSC by physical and chemical methods.…”
Section: Preparation and Validation Of The Decellularized Spinal Cord...mentioning
confidence: 99%
“…Ideal biomaterials with soft mechanical characterizations, oriented three-dimensional structures, high water content and strong deformation resistance are more favorable for the repair of spinal cord tissues. 32,33 Natural DSC had unique advantages: it had the closest biological components to spinal cord tissue and had good biocompatibility, 34 it had cell membrane receptor recognition sites on the surface that facilitated cell adhesion, growth, and survival, 35 it retained molecules such as collagen, fibronectin, laminin, etc., which can bind to integrins on the surface of the proximal growth cone when implanted in vivo, thereby acting as a short-range axon guiding signal. 17 First, we prepared a rat DSC by physical and chemical methods.…”
Section: Preparation and Validation Of The Decellularized Spinal Cord...mentioning
confidence: 99%
“…Due to the nanometer size of NMs, they can not only easily carry drugs or molecules across the blood-spinal cord barrier to target tissues and cells, but also directly modulate the biological effects related to axonal regeneration, ultimately exerting therapeutic effects on SCI ( Kim et al, 2017 ; Domínguez-Bajo et al, 2019 ). However, many studies have shown that NMs play an important role in nerve regeneration after SCI, mostly in the form of scaffolds to load therapeutic drugs or provide regeneration space ( Zhao et al, 2018 ; Woods et al, 2022 ), and few people pay attention to unveil the intrinsic role of NMs in nerve regeneration. In this study, ZnO NPs function both as a natural product and as a nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
“…Both cross-linkers are added in excess and are calculated as follows: EDAC = 0.8 g × total mg HyA in solution; adipic acid = 9.16 g × total mg HyA in solution (Luo, Kirker, & Prestwich, 2000;Woods et al, 2022).…”
Section: Manufacture Hyaluronic Acid Solutionsmentioning
confidence: 99%
“…A key advantage of freeze-dried scaffolds is the ability to easily tune physicochemical properties for specific applications (Woods et al, 2022). It is essential to fully characterize the produced scaffolds before embarking on a series of experiments to monitor any batch-to-batch variance and clearly understand the impact the surrounding physical environment may play on resultant cell behavior.…”
Section: Scaffold Characterizationmentioning
confidence: 99%
See 1 more Smart Citation